he Influence of Non Performing Loans (NPL), Operating Expenses and Operating Costs (BOPO), Loan to Deposit Ratio (LDR) on Return on assets (ROA) - Saputro, Rahma Dani Aji; Trisnia Widuri; Kukuh Harianto (Patua : Journal of Business Administration and Management, 2026)
This study aims to analyze the effect of Non Performing Loan (NPL), Operating Expenses to Operating Income (BOPO), and Loan to Deposit Ratio (LDR) on Return on Assets (ROA) in conventional commercial banks. The method used in this study is panel data regression with a quantitative approach. The research sample was determined using purposive sampling technique and processed using EViews software13. The results show that Non-Performing Loan (NPL) has a positive but not significant effect on Return on Assets (ROA), Operating Expenses to Operating Income (BOPO) has a negative and significant effect on ROA, and Loan to Deposit Ratio (LDR) has a negative but not significant effect on ROA. Simultaneously, NPL, BOPO, and LDR have a significant effect on ROA. These findings indicate that bank profitability is not only influenced by a single factor, but also by a combination of credit risk, operational efficiency, and liquidity. Therefore, optimal management of these three aspects is essential in improving banking profitability performance.